2012
DOI: 10.1593/tlo.12211
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Inhibitors NVP-AUY922 and NVP-BEP800 May Exert a Significant Radiosensitization on Tumor Cells along with a Cell Type-Specific Cytotoxicity

Abstract: Targeting heat shock protein 90 (Hsp90) provides a promising therapeutic approach to enhance the sensitivity of tumor cells to ionizing radiation (IR). To explore the impact of scheduling drug-IR administration, in the present study, we analyzed the response of lung carcinoma A549 and glioblastoma SNB19 cells to simultaneous drug-IR treatment followed by a long-term drug administration. Cellular response was evaluated at different time intervals after IR-alone, drug-alone, or combined drug-IR treatments by col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…A number of anticancer agents including several inhibitors of Hsp90 are known to synergistically enhance the cytotoxicity of IR. Numerous studies, including our own, have already explored Hsp90 as a potential target for tumor cells' radiosensitization [9–11]. A major drawback of Hsp90 inhibition, however, is that it causes up-regulation of Hsp90 itself and his major co-chaperone Hsp70, thereby promoting cell survival by inhibition of caspase-dependent and –independent cell death [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of anticancer agents including several inhibitors of Hsp90 are known to synergistically enhance the cytotoxicity of IR. Numerous studies, including our own, have already explored Hsp90 as a potential target for tumor cells' radiosensitization [9–11]. A major drawback of Hsp90 inhibition, however, is that it causes up-regulation of Hsp90 itself and his major co-chaperone Hsp70, thereby promoting cell survival by inhibition of caspase-dependent and –independent cell death [13].…”
Section: Discussionmentioning
confidence: 99%
“…It also exhibits strong antiproliferative activity against various tumor cell lines and primary tumors in vitro and in vivo at well-tolerated doses [31]. We have shown previously that NVP-AUY922 can radiosensitize diverse tumor cell lines [10, 11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Hsp90 inhibitors are known to affect the cell cycle checkpoint (19, 2124, 35, 36), as does irradiation, which causes a G1/S arrest in P53 WT cells (37), we next determined the interaction of radiation with ganetespib on the cell cycle effects in both H460 and A549 cells (Figure 3A–D). G2/M arrest was induced by ganestepib, radiation, and the combination, at 4 hours postirradiation.…”
Section: Resultsmentioning
confidence: 99%
“…These sensitizing effects are the result of the Hsp90 inhibitor-mediated abrogation of the G2 checkpoint, apoptosis and the inhibition of DNA repair. Studies have shown that one of the causes of sensitization could be inhibition of DNA double strand break (DSB) repair (1721, 36). Checkpoint arrest mainly at G2/M phase has also been suggested as a cause of radiosensitization with Hsp90 inhibitors (1924, 36).…”
Section: Discussionmentioning
confidence: 99%